Assessing the Effects of Tax Elasticity on Government Spending - Debasis Patnaik; Venkat Yaji (International Journal of Engineering and Management Research, 2018)
This paper assesses the effects of Tax elasticity on Government Spending state wise from 2001-2010 for five major states in terms of population. OLS Regression model is used where the relationships are assumed to be linear. The variables used in the regression model are: Gt = the government spending at the state level, the dependent variable Yt = the Gross Domestic Product (GDP) of the state Ct = the central assistance to the state , Et = the elasticity variable, The subscript ‘t’ refers to the corresponding year of analysis and b0, b1, b2, b3, b4, b5 are regression coefficients. In most of the cases, elasticity bore a positive and significant relation to the level of government spending except in the case of Bihar, where the coefficient was negative and insignificant.